THE EFFECT OF INTERNAL CONTROL SYSTEM AND VILLAGE APPARATUS COMPETENCE ON VILLAGE FUND MANAGEMENT ACCOUNTABILITY - Afifi, Zaenal; Mulyanto, Mulyanto; Nugroho, Dennyca Hendriyanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to obtain empirical evidence of the effect of the internal control system on the accountability of village fund management, to obtain empirical evidence of the effect of village apparatus competence on village fund management accountability. The population in this study is village officials in all villages in Kudus Regency. The total number of village officials in all villages in Kudus Regency is 492 people. The results of the analysis show that the test of the influence of the internal control system on the accountability of village fund management shows a coefficient value of 0.207 with a positive direction and p-value = 0.014